Notes on the application of the Peruvian environmental standard over time - de la Puente Brunke, Lorenzo (2018)
The purpose of this article is to analyze the environmental regulation in force in the country with regards to its compliance with the general principles of Law that govern the application of standards over time; this is: the principles of legal security, the non-retroactivity of the rules and the principle of progressiveness or graduality. For this purpose, the author will recount the national environmental legislation from the Environment and Natural Resources Code of 1990, as well as develop key concepts such as environmental quality standards and the aforementioned principles.